PENGARUH PEMASARAN JEJARING MEDIA SOSIAL DAN KETERKAITAN KONSUMEN TERHADAP NIAT BELI KONSUMEN - Rudyanto Rudyanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this study examines the influence of social media and consumer engagement and customer purchase intention. This study uses data taken from 253 users of social media sites in Indonesia. The hypothesis was tested using a structural equation model which was developed in accordance to existing literature reviews. The results show that social media is significantly related to consumer purchase intentions, where consumer engagement acts as a mediating variable in influencing social media users to have customer purchase intentions. The research reinforces that marketers must respond to the importance of increasing of social media usage because it has a strong influence on consumer purchase intentions. The managerial suggestion that can be applied by company is to constantly monitor consumer engagement by adjusting the company's social media marketing strategy. The limitation of this research is the absence of qualitative approaches, i.e. interview to gain a deeper understanding of consumer insights and experiences that may affect consumer purchasing commitments and intentions might help to refine future researches better. In addition, the future research should add other important variables such as of trust, commitment, and e-WOM and any other marketing strategy that might be applied by social media strategists.